2002
DOI: 10.1002/ajmg.10188
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral phenotypic variation in autism multiplex families: Evidence for a continuous severity gradient

Abstract: Recent genetic investigations of autism have studied multiplex families, typically including families with multiple siblings who meet criteria for a diagnosis of autism. However, little is known about the specific behavioral characteristics of siblings with autism in these multiplex families. We investigated the behavioral phenotypic variability and similarity of 351 siblings with autism in 171 multiplex families using cluster analysis and correlations. The results of cluster analyses showed that the individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
146
1
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(164 citation statements)
references
References 46 publications
15
146
1
2
Order By: Relevance
“…In most studies of the parents of children with ASDs a cognitive impairment could not be established. [12][13][14][15][16] An understanding of the extent to which autistic traits and IQ share genetic and environmental factors is important for classifying ASDs as well as for locating and identifying genes that contribute to ASDs. Surprisingly, there is no other published study on twins that assesses the relationship between autistic traits and IQ.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies of the parents of children with ASDs a cognitive impairment could not be established. [12][13][14][15][16] An understanding of the extent to which autistic traits and IQ share genetic and environmental factors is important for classifying ASDs as well as for locating and identifying genes that contribute to ASDs. Surprisingly, there is no other published study on twins that assesses the relationship between autistic traits and IQ.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for underlying behavioral phenotypes has been mixed. Some studies have identified distinct clustering of symptoms (Cuccaro et al, 2003;Tadevosyan-Leyfer et al, 2003), while others have found one, continuously distributed underlying factor (Constantino et al, 2003;Spiker, Lotspeich, Dimiceli, Myers, & Risch, 2002). Cuccaro et al (2005) report that African-American children with autism may have more impaired language development than white children, while oral communication with Lord (2005, oral communication) suggested no such differences.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes referred to as the broader autistic phenotype (BAP) or the lesser variant, these deficits are not severe enough to justify the full diagnosis of autism. In order to investigate the familial aspects of AS and determine its degree of relatedness to autism, it is important to perform studies focusing on large series of probands with AS (Spiker, Lotspeich, Dimiceli, Myers, & Risch, et al, 2002). The purpose of this study is to address this issue.…”
Section: Introductionmentioning
confidence: 99%